Dialectics, totality and the genesis of morinian thought: A brief analysis (Research, Society and Development, 2021)
In the preface to the book "Introduction to Complex Thinking", written in 1990, Edgar Morin addresses the main illusions that keep spirits away from the problem of complex thinking. In this sense, this article discusses the theoretical relationship between dialectic, both Hegelian and Marxist, visualizing the notion of totality and the theory of complexity developed by Edgar Morin. The work was carried out through bibliographic research in scientific articles, books and other documents that address the theme. It brings with it the thoughts of authors such as Konder (1984), Loureiro (2012), Lukács (1989) and Morin (2005), among others. The work is concluded by proving that complexity supersedes the notion of totality through the presence of dialogic in Morinian thought. Unlike Marxian and Hegelian dialectics, it was found that the dialectic for Morin is not conceived as a method that aims to explain phenomena, but discusses complex thinking by demonstrating a continuous dialogue with the uncertainties of the world.